Structural similarities and differences between the human and the mouse pancreas - Dolenšek, Jurij (Islets, 2015)
Mice remain the most studied animal model in pancreas research. Since the findings of this research are typically extrapolated to humans, it is important to understand both similarities and differences between the 2 species. Beside the apparent difference in size and macroscopic organization of the organ in the 2 species, there are a number of less evident and only recently described differences in organization of the acinar and ductal exocrine tissue, as well as in the distribution, composition, and architecture of the endocrine islets of Langerhans. Furthermore, the differences in arterial, venous, and lymphatic vessels, as well as innervation are potentially important. In this article, the structure of the human and the mouse pancreas, together with the similarities and differences between them are reviewed in detail in the light of conceivable repercussions for basic research and clinical application.